Geguritan Nabi Muhammad: Cermin akulturasi budaya Hindu-Islam di Bali - I Nyoman Weda Kusuma, (Universiti Kebangsaan Malaysia, 2007)
Hindu Balinese and Muslims settlers who came to Bali several centuries ago interacted strongly with each other, culturally and socially, and the influence each exerted on the other can be seen in the fact that many Balinese manuscripts contain Islamic nuances. Among these are Geguritan Nabi Muhammad, which is about the worshipping of Allah and Sang Hyang Widhi (the supreme god for Hindu), found in the beginning of the poem GNM. The existence of temples (Pura- Pura the holly place for Hindu) in Bali to worship important Islamic figures also testifies to this hybridity